Cognitive authorities of COVID-19 information: educational differences and outcomes of trust in health experts and social media influencers in Finland - Malinen, Sanna; Koivula, Aki (Information Research an international electronic journal, 2024)
Introduction. This study investigates people’s trust in institutional healthcare experts and social media influencers as sources of COVID-19 information. Using the notion of ‘cognitive authority’, this study examines trusted information sources during the pandemic, how the education level explains this trust, and how trusted COVID-19 information sources are associated with people’s attitudes towards vaccines. Method. Data were collected through eight rounds of nationally representative repeated cross-sectional surveys in 2021. The data set included 8507 respondents from Finland. Analysis. A descriptive analysis was conducted to understand how trust evolved throughout the pandemic. Then, linear probability models were employed to analyse the factors shaping trust and determining vaccine intention. Finally, the analysis examined the indirect effects of trust in the association between education and vaccine uptake. Results. Education explains trust in institutional experts or social media influencers: Those with lower education are more likely to trust social media influencers, and their trust in them is connected to negative attitudes towards vaccines. Conclusion. The findings confirm that people rely on institutional experts and healthcare professionals during a health crisis. Our primary concern is the 5% who trust social media influencers and distrust health experts. The alternative information and low trust in institutions presented by social media influencers can disproportionately affect citizens with a lower level of education.